SEQUÊNCIA DIDÁTICA INTERATIVA PARA O DESENVOLVIMENTO DO PENSAMENTO LÓGICO-MATEMÁTICO NA EDUCAÇÃO INFANTIL - Cerentini, Simone de Arrial (2022)
This research was carried out within the environment of the Franciscan University’s Professional Master´s Degree in Teaching of Sciences and Mathematics, in the Teaching and Learning of Sciences and Mathematics line of research. The research problem that was answered was the following: how can an Interactive Lesson Sequencing (ILS) contribute in the development of the mathematical and logical reasoning in Early Childhood Education? From this research problem, the general objective is to analyze how ILS can contribute in the development of the mathematical and logical reasoning in Early Childhood Education (ECE). In this perspective, discussions were established regarding Interactive Lesson Sequencing (OLIVEIRA, 2013; KINDEL, 2012); Brazilian National Common Core Curriculum (BNCCC) and the Early Childhood Education’s experience fields (BRASIL, 2017); development of mathematical and logical reasoning and Vygotsky’s theory (VYGOTSKY; LURIA; LEONTIEV, 1988; VYGOTSKY, 2004; 2008). A qualitative approach, of exploratory nature, was adopted. Data collection instruments were the registers from children and from the teacher as a researcher of Early Childhood Education, that were analyzed according the Content Analysis (BARDIN, 2011). The study has an education product an Interactive Lesson Sequencing with the exploration of the experience field named “Spaces, times, quantities, relations and transformations” with small children (from 4 to 5 years and 11 months of age). Categories of analysis were: a) Potentialities of the ISL to the development of mathematical and logical reasoning within ECE: it allows for betterment for learning conditions of students about scientific and mathematical concepts and makes them active participants at the knowledge construction, causing them to be curious; b) Challenges of the ILS to the development of mathematical and logical reasoning within ECE: the infrastructure for the making of a vegetable garden and labor to help in the organization and construction of flowerbeds. These two factors that, many times, make difficult the realization of this type of project in schools. It was verified that there is the contribution of ILS within the construction of mathematical and logical reasoning in Early Childhood Education, according to the activities that were carried out.